Impact of Euro-American Crisis on Italian Labor Market : The Case of Young People (Generation) - Aslanov, Asif; Slaný, Martin, 1982-; Prokop, Jaromír; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2018)
This thesis investigates the impact of the 2008 global financial and economic crisis on the situation with Italy’s youth labour market. The findings of the thesis prove that the global crisis had major adverse effects for the Italian economy and boosted negative tendencies which had been previously prominent in the Italian labour market, namely on its youth segment. The regression analysis model developed within this thesis proved itself to be invalid, showing that shifts in Italy’s youth unemployment cannot be explained effectively by shifts in the country’s GDP. Nevertheless, the thesis illustrates how the deterioration in Italy’s economic situation affected its youth labour market in 2008-2009, and what long-standing detrimental effects it had for the country.
Vedoucí práce: Martin Slaný
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses